Peran Customer Satisfaction dalam Memediasi Pengaruh Service Quality dan Customer Value Terhadap Repurchase Intention pada Bengkel AHASS Honda Jl. Kusuma No. 14 Kebumen - Moh Awaludin khamid (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2023)
This research aims to test and analyze the role of customer satisfaction as an intervening variable between service quality and customer value on repurchase intention among Honda AHASS Kebumen workshop customers. The population of this research is the customers of the AHASS Honda workshop on Jl. Kusuma No. 14 Kebumen with 100 customers. Data analysis techniques use descriptive and statistical analysis techniques including validity testing, reliability testing, classical assumption testing, hypothesis testing, correlation analysis and path analysis with the help of the SPSS for Windows version 24.0 program. The results of the research show that service quality has a positive and significant effect on customer satisfaction, customer value has a positive and significant effect on customer satisfaction, service quality has a positive and significant effect on repurchase intention. Customer value has a positive and significant effect on repurchase intention, and customer satisfaction has an effect on repurchase intention and customer satisfaction is able to mediate the relationship between service quality and customer value on repurchase intention.